If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(-8x)=0
We simplify the equation to the form, which is simple to understand
-7(-8x)=0
Reorder the terms in parentheses
+(+56x)=0
Remove unnecessary parentheses
+56x=0
We move all terms containing x to the left and all other terms to the right.
+56x=0
We simplify left and right side of the equation.
+56x=0
We divide both sides of the equation by 56 to get x.
x=0
| 6x^2+36x+51=0 | | 6(7y-4)-(7y+6)= | | 2r+9-9r=3 | | 12x^2-16x^2+20x= | | M=-3(2,-11) | | 4x+7y-9z=14 | | 9y^2-80y+92=0 | | X+2(x)=51 | | 4(3y-1)=12y-4 | | 2(x)^(1/2) | | -2x-5=-4x+5 | | h(t)=-16t^2+15t+8 | | 1/3o12 | | 30x/3x | | 1/2(21)(32) | | B^2-14b+32=0 | | 3x+23y=-29 | | 6x+14=70 | | 258=6(1+7m) | | 4(3r+4)(r+2)=0 | | 4(-m+8)= | | 12/n=72/108 | | 0.18x+0.6(x-5)=0.01(4x-1) | | 32x5=(1/16)4x−3 | | 4(x-5)=7x-27 | | k^2+11k=14 | | n/12=5/15 | | 1/3x/3-1/6 | | 2.95x=28 | | 1(-y-8)= | | -1(-6w-10)= | | 2(7y-4)-(4y+9)= |